In Love with a Cold Climate: Representations of the North in Nineteenth-Century Travel Writing from Scandinavia - Ryall, Anka (Journal of Northern Studies, 2014)
This essay discusses representations of the North in late eighteenth and nineteenth century travel narratives from Scandinavia. It takes as its starting point the traditional conflation of the North with cold that has permeated travellers’ views of Scandinavia, and shows how this stereotype persists even when it is contradicted by the actual experience or observations related in northern travelogues. From some examples of the tension between a real and imaginary North in a selection of travelogues, the essay moves on to look at the aesthetics of the northern landscape in terms of the concepts of the sublime and picturesque. It then shows how an idealising aesthetic emphasis is modified in many northern travel narratives by a foregrounding of realistic details that function as markers of an “anti-aesthetics” of the everyday or commonplace, and give readers a sense of the locally specific and specifically northern in descriptions of places, landscapes and human encounters. It concludes with an example that indicates how an acknowledgment of the aesthetic qualities of everyday human activities such as the dried fish trade helps to undermine the stereotype of the cold, barren, desolate and distant north.